Raw and pasteurized milk quality of D-farm milk processing unit at Faculty of Animal Science, IPB University - Arief, Irma Isnafia; Wulandari, Zakiah; Soenarno, M. Sriduresta; Murtini, Devi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
The Faculty of Animal Science, IPB University, produces pasteurized milk daily under the D-farm milk processing unit. In order to maintain the product quality, as well as its safety, the fresh milk as raw the main material and the produced pasteurized milk quality is tested periodically. The aim of this research is to evaluate the quality of fresh and pasteurized milk produced by the D-farm milk processing unit. The tested fresh milk was originated from two different farms, while the tested pasteurized milk was made by using pasteurizer machine and double-wall pan heating. The tests were carried out by using a lactoscan milk analyzer. The results showed that the fresh milk used by the D-farm milk processing unit had good milk quality, even though still below the SNI standard, while the produced pasteurized milk has met the SNI standard. In addition, the pasteurization by using pasteurizer produced better pasteurized milk quality compared to the traditional pasteurization by using double-wall pan heating.